Legal Basis and Readiness of the Banking Sector in Implementing Privacy Reliability Certification - Amirulloh, Muhamad; suparman, Eman; Novianty Muchtar, Helitha; Hasanah, Hetty (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
There is a disharmony between PBI PKBI and PADG PKBI with the PDP Law, P2SK Law, SPK Law and PBSSN Common Criteria in terms of regulating the obligation to use privacy reliability certificates by financial sector business actors under BI, so that there are many cases of customer personal data breaches. By using normative and empirical juridical methods, this study analyzes efforts to harmonize the regulations related to privacy certification obligations in the financial sector under BI. The results of the study show that with grammatical, systematic, and teleological legal interpretation, PBI PKBI and PADG PKBI can be harmonized regarding the privacy reliability certificate as the legal object in question and the nature of the regulatory norms, but it is not harmonized regarding the status of the privacy reliability certificate as a mandatory SNI, because both PBI PKBI and PADG PKBI as technical regulations in the perspective of the SPK Law have not stipulated SNI ISO 15408-2, 15408-3, or 15408-5 as the referenced standard.